Innovations In Medical Service Improvement: A Comprehensive Review Of Quality Enhancement Models In Healthcare Systems (The Review of Diabetic Studies, 2025)
Healthcare systems around the world are undergoing rapid transformation driven by the need to improve quality, enhance patient outcomes, and ensure cost-effectiveness. This review aims to provide a comprehensive analysis of quality enhancement models and innovative approaches that have been implemented to improve medical service delivery across healthcare systems globally. A systematic review methodology was employed to identify peer-reviewed studies published between 2016 and 2024, focusing on models such as Lean, Six Sigma, Total Quality Management (TQM), Value-Based Healthcare, and Patient Safety Frameworks. The findings revealed that quality improvement models significantly contribute to reducing medical errors, optimizing clinical performance, increasing patient satisfaction, and improving operational efficiency. Additionally, the integration of digital technologies—such as artificial intelligence, telemedicine, and electronic health records—has accelerated innovation in care delivery by facilitating real-time data analytics and personalized care pathways. Despite these advances, barriers such as inadequate infrastructure, resistance to change, and financial constraints continue to hinder full-scale implementation in many regions. This review concludes that a hybrid approach integrating traditional quality models with modern technological innovations offers the most effective pathway to advancing medical service excellence and achieving sustainable healthcare transformation.